If welfare contracts are the solution – then what is the problem? - Foged, Søren Kjær; Hjelmar, Ulf; Jakobsen, Mads Leth (Politica, 2011)
The government, in collaboration with three municipalities, has established welfare contracts in elder care in the period 2021-2024. Through exemption from rules and greater room for maneuver for public employees, it is the ambition to develop new ways of governing the public sector as part of the so-called Subsidiarity Reform. We examine what governance problems employees and managers point to in the three municipalities. We analyze how large and uniform the problems are assessed to be and whether there are patterns in the problems. The article discusses whether the governance tools inherent in the welfare contracts are an obvious solution to the governance problems. The analysis is based on a survey among employees and immediate managers in the three municipalities with welfare contracts in elder care.